Ideals, images and real lives: Women in literature and history - Maithreyi Krishnaraj; Thorner, Alice (Orient Longman, 2000)
Women studies as a distinct field emerged in India in the mid - seventies. But preoccupation with the position of women dates back to more than a century and a half. By the use of methods of history, literary criticism and analysis of discourse, this volume seeks not only to illustrate the broadening of the sphere of women studies in India in recent years, but also to point to the need for relating ideas about women and gender relations to the social and economic forces that shape history.